PENGARUH DUKUNGAN MERTUA DENGAN PEMBERIAN ASI EKSKLUSIF DI RSU AGHISNA MEDIKA KROYA - Ayuningtyas, Beby Yohana Okta; Oktanasari, Wiji; Fitriyani, Tanti (Ensiklopedia of Journal, 2024)
The only food and drink that babies' nutritional needs may be satisfied with for the first six months of their lives is exclusive breast milk, with the exception of vitamins, minerals, and medications. In addition to monitoring the baby's growth each month and making sure the breastfeeding mother eats a healthy diet, mothers can give breast milk whenever the infant requests for it. The mother-in-law's support is what determines exclusive breastfeeding the most. The mother-in-law's responsibilities include helping to express breast milk to the kid while the mother is at work, supporting the mother mentally, helping to take care of the child, and helping with housework. (Health Ministry, 2023) The purpose of the study is to ascertain the impact of the mother-in-law's exclusive breast milk support. sort of case-control time survey study methodology. 62 postpartum moms from RSU Aghisna Medika Kroya served as the study's sample. It is a purposeful sampling method. A survey is the instrument that is employed. cross-tabulation of the chi-square statistical test results showing the link between the independent and dependent variables. At RSU Aghisna Medika, the chi square test results, which produced a p value (0.029) < 0.05, demonstrate that the research findings indicate that there is an influence of mother-in-law's support on exclusive breastfeeding. 2.046% of RSU Aghisna Medika Kroya students exclusively breastfeed when their mother-in-law supports them. According to research findings and recommendations, exclusive breastfeeding at RSU Aghisna Medika Kroya is significantly influenced by the mother-in-law's support. It is intended that health professionals will enlighten and educate mothers-in-law or families to raise understanding about exclusive breastfeeding.Keywords: Mother-in-law support, exclusive breastfeeding